Development of a pharmaceutical product categorization framework taxonomy for the South African public healthcare pharmaceutical supply chain—VAN enabled - Mapowo, Newton (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.